ChemInform Abstract: Development of Fluorescent Probes Based on Protection—Deprotection of the Key Functional Groups for Biological Imaging. Issue 36 (September 2015) - Tang, Yonghe; Lee, Dayoung; Wang, Jiaoliang; Li, Guanhan; Yu, Jinghua; Lin, Weiying; Yoon, Juyoung
Abstract Review: 50 refs.